2020
DOI: 10.4085/1062-6050-82-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Algorithm Associated With Return to Sport After Anterior Cruciate Ligament Reconstruction

Abstract: Context Understanding the factors that predict return to sport (RTS) after anterior cruciate ligament reconstruction facilitates clinical decision making. Objective To develop a clinical decision algorithm that could predict RTS and non-RTS based on the differences in the variables after anterior cruciate ligament reconstruction. Design Cross-sectional study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…The SIRSI was adapted from the Anterior Cruciate Ligament–Return to Sport after Injury (ACL-RSI), in which several studies indicated a higher score in those who achieved full RTP. 1 , 3 , 27 , 32 Psychological recovery has shown to be an independent factor of a patient’s physical recovery, as the ACL-RSI score does not correlate with an athlete’s strength and power measures. 34 However, a higher ACL-RSI score may be predictive of further injury.…”
Section: Discussionmentioning
confidence: 99%
“…The SIRSI was adapted from the Anterior Cruciate Ligament–Return to Sport after Injury (ACL-RSI), in which several studies indicated a higher score in those who achieved full RTP. 1 , 3 , 27 , 32 Psychological recovery has shown to be an independent factor of a patient’s physical recovery, as the ACL-RSI score does not correlate with an athlete’s strength and power measures. 34 However, a higher ACL-RSI score may be predictive of further injury.…”
Section: Discussionmentioning
confidence: 99%
“…The SIRSI is an adaptation of the Anterior Cruciate Ligament-Return to Sport after Injury Scale (ACL-RSI), with several studies demonstrating a higher score in those who are able to successfully RTP. 1,3,24,29 Additionally, psychological recovery has been shown to be independent of a patient's physical recovery, as the ACL-RSI score does not correlate with athletes' strength and power measures. 31 However, a higher ACL-RSI score has been shown to be predictive of further injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, assessment of balance dysfunction and appropriate remedial measures are critical in ACLD subjects. 29 The importance of psychological preparedness along with good postural balance and better agonist-antagonist ratio for return to sports are highlighted by Albano et al 30 If balance issues are not addressed during the rehabilitation phase, then, they might continue to persist and increase the risk of re-injury. 31 Limitations of the study: Remarkable gender difference between stydy and control group might have created a gender bias in this study.…”
Section: Discussionmentioning
confidence: 99%